Ag+ release and corrosion behavior of zirconium carbonitride coatings with silver nanoparticles for biomedical devices - Velasco, Sebastian Calderon (2013)
Zirconium carbonitride coatings with silver nanoparticles were produced by DC unbalanced dual magnetron sputtering system, using two targets, Zr and Zr/Ag in an Ar, C2H2 and N2 atmosphere. Stainless steel 316L and silicon (100) substrates were used for electrochemical and structural characterization, respectively. Silver was found to be well distributed throughout the coatings, maintaining the films' composition in depth, while its diffusion to the electrolyte decreases as immersion time increases, stopping its release after 7 to 8 days of immersion. Electrochemical characterization revealed very stable films that have improved base material, without any diminished corrosion resistance due to the silver content.